Does pamidronate enhance the osteogenesis in mesenchymal stem cells derived from fibrous hamartoma in congenital pseudarthrosis of the tibia? - Madhuri, Vrisha (Bone Rep, 2016)
Neurofibromatosis type 1 (NF1) is a commonly occurring genetic disorder in children. Mutation in the NF1 gene has its implication in poor osteoblastic capabilities. We hypothesised that pamidronate will enhance the osteoblastic potential of the mesenchymal stem cells (MSCs) derived from lipofibromatosis tissue of children with congenital pseudarthrosis tibia (CPT) associated with NF1. In this study, bone marrow MSCs (BM MSCs) and CPT MSCs were obtained from three patients undergoing salvage surgeries/bone grafting (healthy controls) and those undergoing excision of the hamartoma and corrective surgeries respectively. The effects of pamidronate (0, 10 nM, 100 nM and 1 μM) on cell proliferation, toxicity and differentiation potential were assessed and the outcome was measured by staining and gene expression. Our outcome showed that CPT MSCs had more proliferation rate as compared to BM MSCs. All 3 doses of pamidronate did not cause any toxicity to the cells in both the groups. The CPT MSCs showed less differentiation with pamidronate compared to the healthy control MSCs. This was quantitated by staining and gene expression analysis. Therefore, supplementation with pamidronate alone will not aid in bone formation in patients diagnosed with CPT. An additional stimulus is required to enhance bone formation.